Ett värdigt liv som funktionshindrad - En analys om rätten att leva som alla andra - Hansson,Tilda (2023)
In 1994, the Swedish law on certain disabled persons, came into effect as a result of the government’s inquiry. The inquiry was named “Handikappreformen” (in english: The Disability reform). The reform revealed disparities between individuals with disabilities and those without disabilities. Furthermore, the inquiry noted that the support received through social services and healthcare was insufficient to create equitable conditions. According to the purpose of the law, conclusively, the individuals with disabilities should be afforded the opportunity to live as dignified life as possible, in relation to other individuals. Furthermore, interventions should be designed to correspond to the individual’s specific needs and enhance their ability to live as independently as possible. The essay is focused on the intervention named “personal assistance” and allowance of personal assistance. The allowance refers to the economic compensation disbursed by Försäkringskassan. To be eligible for personal assistance, the individual’s basic needs must amount to at least 20 hours on average per week. Then, the individual can apply for personal assistance for needs beyond the basic ones. However, this presupposes that the individual actively participates in the intervention alongside their assistant. The analysis will investigate the factors that play a role in the basic needs in light of legal cases and the goal of the Law. It will also highlight the problems associated with the assessment. On one hand, the law itself is effective, on the other hand, its application has become problematic.
Keywords: Socialrätt; Förvaltningsrätt; LSS; Grundläggande behov; Personlig assistans